Crystal structure, spectroscopic studies and non‐linear optical properties of 2‐amino‐3‐nitropyridinium trichloroacetate. Issue 11 (24th July 2015) - Song, Cheng; Zhou, Yuelan; Sun, Zhihua; Chen, Tianliang; Zhang, Shuquan; Luo, Junhua
Abstract : A novel quadratic NLO crystal material 2‐amino‐3‐nitropyridinium trichloroacetate is connected by multiple hydrogen bonds. The SHG efficiency is two times that of KDP and useful for frequency converting in visible region which indicate a potential NLO candidate material. Abstract : A new quadratic nonlinear optical crystal, 2‐amino‐3‐nitropyridinium trichloroacetate (2A3NPTCA), was synthesized and the single crystals were grown by slow evaporation method at room temperature. Single crystal X‐ray diffraction and powder X‐ray diffraction experiments were carried out in order to confirm the structure and crystalline nature of 2A3NPTCA crystal. The chemical bonding and various functional groups present in the 2A3NPTCA were identified from FT‐IR spectrum. The UV–visible–NIR transmission spectrum shows that it is suitable for frequency‐converting in the wavelength region of 431–1200 nm. Thermogravimetric (TG) and differential thermal analysis (DTA) were carried out to characterize the thermal behaviors of the grown crystals. Kurtz and Perry powder method for second harmonic generation (SHG) measurements demonstrate that 2A3NPTCA is a phase matching material and its nonlinear optical efficiency is two times that of KDP. All the above results suggest that 2A3NPTCA is a potential candidate of NLO material.